The role of the capstone project in supporting the job experience of industrial design graduates in the field of work - Prof. Nermin Kamel Mohamed Elgedawy; Associ.Prof. Dr. Hassan Radwan Mohamed; Lect. Eman Shaban Mahmoud Eltabakh (Journal of Architecture, Art & Humanistic Science, 2024)
The capstone project is considered one of the most important contemporary global applications that are offered to university students, through which it is possible to support the academic program for industrial design in Egypt and develop the professional experiences of the graduate who faces great challenges between what he practiced in university life and what he should be in practical and professional life. In the Capstone Project, students work in teams divided into groups of up to 5 students to design, build and test prototypes using real-world applications. The duration of the Capstone Project lasts for two full semesters, and at the end of the semester, students present their efforts they have reached in the design required for a project Graduation This period gives students some time to plan and implement their project, so that the main objective of this project is to test the students' competency and skill level. Thus, the capstone course is an integrated experience for an educational program. Through it, it is possible to think about all the things that were important to the student in university life by solving the most complex problems in the early educational stages. The capstone also helps in preparing the graduation project, which is one of the critical needs of students to help them pass the last semester, which qualifies him for practical life. The capstone course also provides students with privileges by providing opportunities to work with real-world, open-ended and interdisciplinary challenges proposed by sponsors of industrial and research projects. They learn and apply the engineering design process, define functional requirements, conceptualize, analyze, identify risks and countermeasures, and choose between physical models. Based on the above, Capstone courses in industrial design seek to prepare students to solve real-world problems to be more prepared for the workforce. The research paper deals with the definition of the capstone, its importance, characteristics, types and Methodology for the industrial design graduate in career progression, the method of its application and examples of it from some industrial design universities.